Концептуальні засади розвитку біоенергетичного потенціалу фермерських господарств - Єременко, Денис Володимирович; Еременко, Денис Владимирович; Yeremenko, Denys (My University, 2017)
UK: У статті досліджено напрями розвитку біоенергетичного виробництва на базі фермерських господарств. Висвітлено актуальність теми дослідження за сучасних умов. Доведено наявність біоенергетичного потенціалу вітчизняного фермерства як складника аграрного виробництва. Обґрунтовано необхідність системного підходу в процесі розвитку біоенергетичного потенціалу фермерських господарств як невід’ємного складника їх конкурентоспроможності. Проаналізовано соціально-економічні фактори, які впливають на перспективи забезпечення ефективного використання біоенергетичного потенціалу фермерських господарств. RU: В статье исследованы направления развития биоэнергетического производства на базе фермерских хозяйств. Освещена актуальность темы исследования в современных условиях. Доказано наличие биоэнергетического потенциала отечественного фермерства как составляющей аграрного производства. Обоснована необходимость системного подхода в процессе развития биоэнергетического потенциала фермерских хозяйств как неотъемлемой составляющей их конкурентоспособности. Проанализированы социально-экономические факторы, которые влияют на перспективы обеспечения эффективного использования биоэнергетического потенциала фермерских хозяйств. EN: In the article the directions of development of bioenergy production on the basis of farms. The importance of the research topic in modern conditions. The authors noted the following circumstances indicating the importance of this issue. The need to create a self-sufficient non-volatile system of Ukraine at the national and regional levels, justified by the realities of today. Features of economic activities of domestic farmers. The establishment of regional energy centers of subjects of small agrarian enterprises able to exercise significant positive influence on the process of socio-economic development of rural areas. In the article the directions of development of bioenergy production on the basis of farms. The importance of the research topic in modern conditions. Proven bioenergy potential of domestic farming as part of agricultural production. The necessity of a systematic approach in the process of development of bioenergy potential of farms as integral to their competitiveness. Analyzed socio-economic factors that affect the prospects for effective use of bioenergy potential of farms. The author points to the lack of proper infrastructural support of bioenergy production at the level of rural territories. The article notes the poor level of state support for development of bioenergy.
Концептуальные основы развития биоэнергетического потенциала фермерских хозяйств
Conceptual bases of development farms’ bioenergy potential
Keywords: біоенергетика; фермерські господарства; конкурентоспроможне виробництво; аграрний сектор; биоэнергетика; фермерские хозяйства; конкурентоспособное производство; аграрный сектор; bioenergy; farms; competitive manufacturing; the agricultural sector